2007
DOI: 10.1111/j.1095-8649.2007.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in life‐history traits of the endemic kite skate Dipturus chilensis (Batoidea: Rajidae), along its distribution in the fjords and channels of southern Chile

Abstract: Life‐history traits of kite skates Dipturus chilensis were examined from two regions (c. 2286 km apart) in the sheltered fjords and channels of southern Chile. A total of 482 and 403 specimens were collected from the southern fjords (c. 42–46° S) and the fjords of Chilean Patagonia (c. 51–54° S), from September 2003 to 2004, respectively. Vertebra marginal increment analysis indicated an annual deposition of growth rings which was completed during the winter months. For each region, von Bertalanffy growth para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
3
16
0
1
Order By: Relevance
“…There are many hypotheses to explain this fact, these variations could be a consequence of oceanographic conditions, the effect of fishing pressure (Mabragaña, Cousseau, 2004), or the result of phenotypic plasticity (Licandeo, Cerna, 2007). The maximum TL and size at maturity recorded here were similar to that previously reported in northern Patagonian waters and greater than the registered for individuals from southern and southeastern Brazil (Oddone, Vooren, 2005;Oddone et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…There are many hypotheses to explain this fact, these variations could be a consequence of oceanographic conditions, the effect of fishing pressure (Mabragaña, Cousseau, 2004), or the result of phenotypic plasticity (Licandeo, Cerna, 2007). The maximum TL and size at maturity recorded here were similar to that previously reported in northern Patagonian waters and greater than the registered for individuals from southern and southeastern Brazil (Oddone, Vooren, 2005;Oddone et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…However, the size of the egg cases of A. cyclophora examined in this work were similar those recorded by from southern Brazil. According to Licandeo, Cerna (2007), the females of Zearaja chilensis (Guichenot, 1848) of the southernmost distribution from southern Chile would invest more energy in the production of larger egg cases instead of more quantity of eggs, than females of the northern region. More complementary studies of the ovarian fecundity of A. cyclophora are necessary to better understand their reproductive traits.…”
Section: Discussionmentioning
confidence: 99%
“…This reveals differences in reproductive parameters in the species that might be influenced by both life history and environmental traits. Such regional (Yamaguchi et al, 2000;Lombardi-Carlson et al, 2003;Licandeo & Cerna, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Together considering a strong correlation between TL and the radius identified for each sex, it is therefore concluded that all fish reach a similar body size at the first growth band formation (i.e., summer to autumn) regardless of their hatching dates. Although there are several reports on age and growth of skate species with year-round oviposition (Frisk & Miller, 2006;Kadri, Marouani, Bradai, & Bouaïn, 2013;Kadri et al, 2012;Licandeo & Cerna, 2007;Richards, Merriman, & Calhoun, 1963), to our knowledge, this is the first study based on solid evidence reporting such a unique trait in skate. Further studies are Previous studies have suggested that band formation might be related to physiological changes that correspond to the seasonal variation of environmental parameters, such as temperature and photoperiod, as well as the reproductive state (Goldman, 2004;Simpfendorfer, 1993).…”
Section: Discussionmentioning
confidence: 93%